A patient with hypopituitarism and isochromosome 18q mosaicism - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (KARGER, 2005)
Aims: Patients with isochromosome 18 [i(18q)] have features of both trisomy 18 and deletion of 18p [del(18p)] syndromes. Although, hypopituitarism has been reported in patients with del(18p) syndrome, it has not been described in patients with i(18q) syndrome previously. We describe a case with i(18q)/del(18p) mosaicism associated with a novel finding of hypopituitarism. Methods: Clinical characteristics of the patient have been discussed in the light of the literature. Results: The patient had dysmorphic findings that are predominantly seen in del(18p) syndrome such as low nasal bridge, wide mouth, large ears, high forehead, hypopigmentation, upturned nostrils and hypopituitarism (TSH, ACTH, and GH deficiencies, and pituitary hypoplasia on magnetic resonance imaging). In addition, she also had upturning of upper lip and seizures, which are features of trisomy 18 syndrome. Conclusions: In agreement with the previous clinical reports, this case further supports the presence of a factor, which is involved in pituitary development and/or function, on the short arm of chromosome 18. (c) 2005 S. Karger AG, Basel.
Keywords: isochromosome 18q; hypopituitarism; mosaicism of chromosome 18; deletion of 18p; GROWTH-HORMONE DEFICIENCY; MAXILLARY CENTRAL INCISOR; SHORT ARM DELETION; MYELIN BASIC-PROTEIN; TRISOMY-18 MOSAICISM; NORMAL INTELLIGENCE; RING CHROMOSOME-18; PRENATAL DETECTION; SHORT STATURE; MONOSOMY 18P